2023
DOI: 10.11606/s1518-8787.2023057004896
|View full text |Cite
|
Sign up to set email alerts
|

Marcadores do consumo alimentar do Sisvan: estrutura e invariância de mensuração no Brasil

Bárbara Hatzlhoffer Lourenço,
Bianca de Melo Guedes,
Thanise Sabrina Souza Santos

Abstract: OBJETIVO: Caracterizar a estrutura interna do formulário de marcadores do consumo alimentar do Sistema de Vigilância Alimentar e Nutricional (Sisvan) para indivíduos maiores de 2 anos de idade e analisar evidências de invariância de mensuração entre macrorregiões brasileiras, fases do curso da vida e ao longo do tempo. MÉTODOS: Realizou-se análise paralela com estimação de fatores complementada com análise fatorial exploratória a partir de todos os registros de primeiro acompanhamento do Sisvan com respostas v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Although we are not aware of studies that have compared the indicators obtained from the Sisvan questionnaire with more comprehensive methods of collecting data on food consumption, other studies have already shown good agreement between reports of food consumption screeners and estimates from 24-hour recalls 36 , 37 . In addition, recent analyses, also with the objective of providing evidence of validation of Sisvan food consumption markers, indicated that the form has a two-dimensional internal structure for individuals from two years of age, opposing the four items that bring together ultra-processed foods (dimension 1) to those that include fruits, vegetables and beans (dimension 2), and has consistent measurement characteristics across macro-regions, age groups and over the years 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we are not aware of studies that have compared the indicators obtained from the Sisvan questionnaire with more comprehensive methods of collecting data on food consumption, other studies have already shown good agreement between reports of food consumption screeners and estimates from 24-hour recalls 36 , 37 . In addition, recent analyses, also with the objective of providing evidence of validation of Sisvan food consumption markers, indicated that the form has a two-dimensional internal structure for individuals from two years of age, opposing the four items that bring together ultra-processed foods (dimension 1) to those that include fruits, vegetables and beans (dimension 2), and has consistent measurement characteristics across macro-regions, age groups and over the years 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de não termos conhecimento de estudos que tenham comparado os indicadores obtidos do questionário do Sisvan com métodos de coleta de dados de consumo alimentar mais abrangentes, outros trabalhos já mostraram uma boa concordância entre relatos de screeners do consumo alimentar e estimativas de recordatórios de 24 horas 36 , 37 . Além disso, análises recentes, também com objetivo de fornecerem evidências da validação dos marcadores do consumo alimentar do Sisvan, indicaram que o formulário apresenta estrutura interna bidimensional para indivíduos a partir de dois anos de idade, contrapondo os quatro itens que congregam alimentos ultraprocessados (dimensão 1) àqueles que incluem frutas, hortaliças e feijão (dimensão 2), e possui características de mensuração consistentes entre macrorregiões, faixas etárias e ao longo dos anos 38 .…”
Section: Discussionunclassified
See 1 more Smart Citation